Developments in tissue engineering scaffolding using an electrospinning process - Ngadiman, N.; Noordin, M.; Idris, A.; Kurniawan, Denni; Fallahiarezoudar, E.; Sudin, I. (Nova Science Publishers, 2017)
© 2017 Nova Science Publishers, Inc. Electrospinning is a simple and efficient process in producing nanofibers. The use of an electrospinning process in fabricating tissue engineering scaffolds has received great attention in recent years due to its simplicity and ability to fabricate ultrafine nanofibers. Most of the recent progress in tissue engineering has embarked on the use of nanofibers as tissue engineering scaffolds. This is because nanofibers can replicate the structural design of natural human tissue at the nano-scale thus shortening the healing time. Although electrospinning is a simple process, there are still several parameters which need to be controlled or optimised in order to produce nanofibers with different characteristics. Different applications might require nanofibers with specific criteria to be produced. Hence, this review will reveal the fundamental working principles of electrospinning process and the effect of electrospinning process parameters towards the nanofibers morphology. Various polymeric materials and their composites/blends have been successfully electrospun for tissue engineering (TE) scaffolds and they have been tabulated. In many cases, secondary processes are also integrated with the electrospinning process so as to develop 3D TE scaffolds and overcome limitations in term of the nanofiber thickness.